Physician perception of clinical improvement in children with attention-deficit/hyperactivity disorder: a post hoc comparison of lisdexamfetamine dimesylate and mixed amphetamine salts extended release in a crossover analog classroom study - López F; Scheckner B; Childress A (Neuropsychiatric Disease and Treatment, 2011)
Frank A López1, Brian Scheckner2, Ann C Childress31Children's Developmental Center, Winter Park, FL, USA; 2Clinical Development and Medical Affairs, Shire Development Inc., Wayne, PA, USA; 3Center for Psychiatry and Behavioral Medicine, Las Vegas, NV, USA Trial Registry: NCT00557011Objective: To assess effects of lisdexamfetamine dimesylate (LDX) and mixed amphetamine salts extended release (MAS XR) on symptom improvement in children with attention-deficit/hyperactivity disorder (ADHD).Methods: Post hoc analysis of a randomized, double-blind, placebo-controlled, crossover analog-classroom environment was conducted. The primary efficacy outcome was the deportment subscale of the Swanson, Kotkin, Agler, M-Flynn, and Pelham (SKAMP-D) rating scale. The secondary efficacy outcome was the investigator-rated Clinical Global Impressions-Improvement (CGI-I), a 7-point scale ranging from 1 (very much improved) to 7 (very much worse), which assesses improvement over time from baseline. McNemar test was used to compare participants' responses to LDX and MAS XR on CGI-I scores dichotomized into 1 (very much improved) vs all other response scores (2 to 7) in a 2 × 2 table.Results: Fifty-two children (aged 6 to 12 years) were enrolled, titrated, and randomized; 50 completed the study. Investigators rated 74% of LDX participants as either very much improved or much improved on the CGI-I scale relative to 72% of MAS XR participants and 18% of placebo participants. Of the 50 children who completed the study, 32% of LDX participants were very much improved vs 16% of MAS XR, and 2% of placebo participants relative to baseline. McNemar test indicated that 10 participants were very much improved with LDX, but not MAS XR; 2 participants were very much improved with MAS XR, but not LDX; 6 participants were very much improved with both, while 32 were not very much improved with either. Analysis showed that LDX had a significantly higher number of children with a very much improved score on the CGI-I than MAS XR (P = 0.0386).Conclusion: Treatment of children with LDX resulted in a higher number of participants with a very much improved score on the CGI-I than treatment with MAS XR or placebo.Keywords: lisdexamfetamine dimesylate, LDX, Vyvanse, mixed amphetamine salts, extended release, ADHD, CGI-I